2021
DOI: 10.3390/nu13020497
|View full text |Cite
|
Sign up to set email alerts
|

Citrus hassaku Extract Powder Increases Mitochondrial Content and Oxidative Muscle Fibers by Upregulation of PGC-1α in Skeletal Muscle

Abstract: Peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) is expressed in skeletal muscles and regulates systemic metabolism. Thus, nutraceuticals targeting skeletal muscle PGC-1α have attracted attention to modulate systemic metabolism. As auraptene contained in citrus fruits promotes lipid metabolism and improves mitochondrial respiration, it could increase mitochondrial function through PGC-1α. Therefore, we hypothesized that PGC-1α is activated by auraptene and investigated its effect using Citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We focused on strategies to inhibit cholesterol esterification and thus prevent its accumulation, inducing mechanisms that carry out cholesterol to the extracellular media through the transporter ABCA1. ACAT can be regulated by an Aur molecule [28], a geranyloxyn coumarin found in citrus fruits and Ferula species [56]. Based on this evidence and the activity of cholesterol transporters, we focused on the effect of Aur on ABCA1 expression.…”
Section: Regulation Of Intracellular Cholesterol Metabolism By Auraptenementioning
confidence: 99%
“…We focused on strategies to inhibit cholesterol esterification and thus prevent its accumulation, inducing mechanisms that carry out cholesterol to the extracellular media through the transporter ABCA1. ACAT can be regulated by an Aur molecule [28], a geranyloxyn coumarin found in citrus fruits and Ferula species [56]. Based on this evidence and the activity of cholesterol transporters, we focused on the effect of Aur on ABCA1 expression.…”
Section: Regulation Of Intracellular Cholesterol Metabolism By Auraptenementioning
confidence: 99%
“…However, the precise mechanisms by which auraptene inhibits proliferation and increases apoptosis in prostate cancer cells are yet to be identified. It was recently reported that Citrus hassaku extract powder (CHEP) upregulated PGC-1α and increased the mitochondrial content of muscles in mice fed a CHEP-containing diet by promoting SIRT3 expression and AMPK activation [20].…”
Section: Introductionmentioning
confidence: 99%